Analysis of Judge Considerations and Legal Basis in Decisions Rejecting Lawsuits in Land Disputes - Maimunah Maimunah; Amad Sudiro (PT Publikasiku Academic Solution, 2023)
In the land dispute case in decision Number 644/Pdt.G/2020/PN. Tng where the plaintiff filed a lawsuit over a land object which he claimed was inherited from his parents to the defendant who had so far controlled and used the land object. In his decision the judge rejected the plaintiff's claim in its entirety, the judge's refusal was inseparable from the judge's legal considerations which became the basis for a decision. The type of research used is normative legal research. The approach used by the authors in this study is the statutory approach and case approach. The type of data in this study is secondary data. In this study, data analysis was used. is a qualitative analysis. the results of this study are that the judge in his consideration saw the plaintiff's evidence in the form of letter C where the evidence was not strong as confirmed by the decision of the supreme court of the Republic of Indonesia dated 25-61973 no 84 K/Sip/1973 which said notes from the village book (letter C) cannot be used as proof of ownership rights if it is not accompanied by other evidence. The conclusion of this study is that the consideration of the judge in making a decision uses a balance approach and the Ratio Decidendi approach, where the judge considers all aspects related to the subject matter in dispute and then looks for laws and regulations that are relevant to the subject matter in dispute as the legal basis for imposing a decision